Supercapacitor electrodes from activation of binderless green monoliths of biomass self-adhesive carbon grains composed of varying amount of graphene additive - Jasni, MRM; Deraman, M; Suleman, M; Zainuddin, Z; Othman, MAR; Chia, CH; Hashim, MA (Springer Heidelberg, 2024)
Binderless electrodes of activated carbon monoliths (ACMs) and its composites with graphene are prepared by carbonization and activation of green monoliths consisting of self-adhesive carbon grains and 0-10 wt% KOH-treated graphene. Compared with ACMs, the optimized composite containing 6 wt% graphene exhibits more ordered micro-structures with increased crystallite height, and graphitic sp(2) carbons (I (D) /I (G) = 0.49 vs. 0.91) along with enhanced porosity; as revealed by X-ray diffraction, Raman, and N-2 adsorption-desorption studies. These modifications lead to increased electrical conductivity (13 vs. 9 S cm(-1)) through improved interconnections of carbon particles by graphene, and surface area similar to (800 vs. 456 m(2) g(-1)) due to increased inter-particle spacing. Further, contrary to ACMs, the composite electrodes can offer faster delivery of energy in almost 50% less response time (5 vs. 8 s) due to reduced equivalent series resistance (1.67 vs. 2.65 Omega) and charge transfer resistance (0.55 vs. 1.33 Omega).